2023
DOI: 10.1049/itr2.12432
|View full text |Cite
|
Sign up to set email alerts
|

The effect of visibility on road traffic during foggy weather conditions

Faryal Ali,
Zawar Hussain Khan,
Khurram Shehzad Khattak
et al.

Abstract: The impact of fog on visibility is a major factor affecting traffic congestion and safety. This paper proposes a microscopic traffic model that captures the features of traffic in foggy weather and characterizes it based on visibility. The intelligent driver (ID) model is based on a constant acceleration exponent and produces similar traffic behaviour for all conditions, which is unrealistic. The performance of the ID and proposed models is evaluated on a 2.2 km ring road for 250 s with a platoon of 51 vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…When planning travel and daily routines on weekdays, individuals must adhere to stringent timetables for commuting, transporting children to school, attending professional meetings, and more. Consequently, weather conditions become a pivotal factor, influencing decisions like carrying rain gear or allowing extra time to navigate potential traffic delays [19][20][21]. Hence, staying informed about weekday weather is paramount for efficient trip planning.…”
Section: Discussionmentioning
confidence: 99%
“…When planning travel and daily routines on weekdays, individuals must adhere to stringent timetables for commuting, transporting children to school, attending professional meetings, and more. Consequently, weather conditions become a pivotal factor, influencing decisions like carrying rain gear or allowing extra time to navigate potential traffic delays [19][20][21]. Hence, staying informed about weekday weather is paramount for efficient trip planning.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, some of the light is lost or reflected back towards road users in the form of a veil of fog that obscures details of the road ahead [8]. This decrease in visibility due to fog results in a decrease in the driver's visual and operating abilities, threatening safe driving [9,10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, there are research cases that have identified through subject experiments that obstacle recognition distance increases as lighting performance improves [20], and there are studies that have identified through empirical experiments that obstacle recognition distance can change by applying various road lighting during adverse weather [9]. Additionally, there are empirical research results showing that the higher the color temperature of road lighting during fog, the higher the obstacle visibility [21].…”
Section: Literature Reviewmentioning
confidence: 99%